Growth and yield of castor bean when consorted with crops and green manure - Rando, Eduardo Meneguel; Quintanilha, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
- A field experiment was carried out at Bandeirantes, PR, Brazil, in 1984-1985, to study the development and grain yield of Ricinus communis L. when consorted with crops and green manure. The treatments were: two and three tines of Phaseolus vulgaris L., two and three lines of Arachis hypogaea L., one line of Zea mays L., one and two lines of Canavalis ensiformis D.C., one and two lines of Stizolobium deeringianum Steph and Bart. The distance between the limes of Ricinus communis L was mantained constant with 2,5 m. Although the effects were more evident in the first harvest, the total grain yield of Ricinus communis L. was decreased as a consequence of the intereropping system used. The most restrictive effect observed was induced by Canavalia ensiformis D.C. (two tines seeded), that reduced with high statistics significance the total production of Ricinus communis L